Algebraic Expression

Download as doc, pdf, or txt
Download as doc, pdf, or txt
You are on page 1of 25

ALGEBRAIC EXPRESSION

1 p+p= 2 2b + b = 3 a + 3a =

4 3y + y = 5 6m + 5m = 6 3c + 2c =

7 6x + 4x = 8 y + 10y = 9 3r + 7r =

10 5m + 2m = 11 m + 10m = 12 2c + 13c =

13 7c + 7c = 14 p + 12p = 15 6r + 3r =

16 3k + 10k = 17 r + 16r = 18 3p – p =

19 7k + 9k = 20 6b + 7b = 21 8a – 2a =

22 6y – 3y = 23 3pq – pq = 24 7k – 2k =

25 10k – k = 26 7m – m = 27 2ab – ab =

28 6x – 6x = 29 20y – 13y = 30 7p – 3p =

31 –x + 3x = 32 –x + 5x = 33 x + 10x =

34 –2x + 5x = 35 –7p + p = 36 –10y + 3y =

37 –2x + 3x = 38 –6x + 3x = 39 –8a – 10a =

40 10cd – 3cd = 41 3xy + 2xy = 42 4ab + 3ab =

43 2mn + mn = 44 4pq + pq = 45 3pqr + 6pqr =

46 6c + _____ = 10c 47 3a + _____ = 8a 48 3p + _____ = 10p

49 _____ + 2cd = 4cd 50 _____ + 7ab = –2ab 51 _____ – 4mn = 5mn


ALGEBRAIC EXPRESSION(Simplify each of the following)

1 7 w  3  2w = 2  4t  2  t = 3 2 p  3q  p  7 q =

4  7 h  4  2h  9 = 5 2k  3  11k  8 = 6 u  5  2u  7 =

7  5x  6  8x = 8  14 p  5  6 p = 9  5 y  2x  y  x =

10 5  2a  3a = 11  10  2 f  7 f = 12 3x  5 x  y  4 y =

13 7 x  4 y  2x  5 y = 14 2a  5a  b  3b  2 = 15 5a  2b  2a  b =

16 6p  q  p  q= 17 5x  3y  x  y = 18 3m  2n  m  5n =

19 2x  y  x  5 y = 20 5a  2b  3a  b  3b = 21 2 p  16  4 p  10 =

22 3x  4 y  2 x  6 y = 23 3 p  2q  6 p  1 = 24  16u  1  9u =

25 9 r  3  5r  8 = 26  2c  10  6c  4  2d = 27 7  4e  f  8e  6 f =

28 3r  10  2r = 29 y  7  2y  3= 30 15u  7v  8u  10v =

31 10  8 x  2  7 x = 32 10 y  5  4 y  2 = 33 3 p  8  5 p  11 =

34 3h  12  9  5h = 35 6r  5  r  3 = 36 8k  3  11  13k =

37 8a  11  2a = 38 9x  5  4x = 39 8m  12  m  3 =

40 6u  8v  2u  3v = 41 9 s  8  7t  4 s = 42 8x  5  3x  8 =

43 10  4m  3  m = 44 8m  9k  7 k  5m = 45 p  2p  5  3p =

46 7 h  5k  3h  h  47  3d  5  2d  d = 48 hk  3h  5hk  4k =

49 9ab  8a  3  ab = 50 6mn  2 xy  xy  3mn  8 = 51 3 xy 2  5 z  6  xy 2  3  4 z =


ALGEBRAIC EXPRESSION( Expand each of the following)

1 2 a  b  = 2 5 x  y  = 3 7 c  d  =

4 2 2a  b  = 5 5 x  3 y  = 6 7  4c  d  =

7 3 3 p  2q  = 8 4 2 x  3 y  = 9 5 4a  5b  =

10 6 5e  7 f  = 11 2 a  b  c  = 12 3 x  y  z  =

13 2 2a  b  c  = 14 3 3 x  2 y  z  = 15 4 2 x  3 y  z  =

16 3 a  b  = 17 2 x  y  = 18 2 2a  b  =

19 7 c  d  = 20 5 3 y  x  = 21 3 4c  d  =

22 7 3 p  2q  = 23 5 2 x  3 y  = 24 4 4a  5b  =

25 6 7 f  5e  = 26 2 a  b  c  = 27 3 x  y  z  =

28 2 2 a  b  c  = 29 3 3 x  2 y  2 z  = 30 4 2 p  q  3r  =

31  2 a  b  = 32  3 x  y  = 33  4 2 x  y  =

34  5 2a  b  = 35  6 3 p  2q  = 36  2 a  b  =

37  3 x  y  = 38  4 2 x  y  = 39  5 2a  b  =

40  6 3 p  2 q  = 41   a  b  c = 42  3 x  4 y  7 z  =

43  4 5  7 x  4 y  = 44  2 x  2 y  7  = 45  3 v  5w  9  =

ALGEBRAIC EXPRESSION( Simplify each of the following)

1 6  2 2n  8 = 2 8  3 v  2  = 3 8  2 n  5  =
4 7  2 x  1 = 5 5  2 w  6  = 6 18   2  m  =

7 14  3 3  2 x  = 8 2h  3 2h  2  = 9 5m  3 2  m  =

10 3 p  4 2 p  3 = 11 5  21  v  = 12 3 2 f  5   3  2 f  =

13  2 p  3   4  3 p  = 14  4e  3  6 e  2 = 15 3 f  1   4 f  7  =

16  3b  1   2b  7  = 17  2 p  3   4  3 p  = 18 5 3 p  3  3 2 p  7  =

19 5 3 p  3  3 2 p  7  = 20 7 2 p  1  4 3 p  2  = 21  9 y  3 y  2  =

22 2 x  2 3  x  = 23  2x  y   x  5 y = 24  16u  1  9u =

25 3 m  2 m  4   = 26  7 x  4 x  5 = 27  4 3  q   6q  2 =

28 4 2 x  4 x  3  = 29 7q  3  5 2  q  = 30  3h  4 6  5h   7 =

31  61  2 x   4 x  10 = 32  4e  3  6 e  2 = 33 14  3 3  2 x  =

34 6  2 2n  8 = 35 3 f  1   4 f  7  = 36 5m  3 2  m  =

37  3b  1   2b  7  = 38 8  2 n  5 = 39 7 2 p  1  4 3 p  2  =

40  2 p  3   4  3 p  = 41 5 3 p  3  3 2 p  7  = 42 3 p  4 2 p  3 =

43 8  3 v  2  = 44 18   2  m  = 45 2h  3 2h  2  =

46 5  21  v   47 3 2 f  5   3  2 f  = 48 4 2 x  y    8 x  4 y  =

TICKET 1(a) TICKET 1(a) TICKET 1(a)


Simplify each of the following Simplify each of the following Simplify each of the following
(a) p+p (a) p+p (a) p+p
(b) 2b + b (b) 2b + b (b) 2b + b
(c) a + 3a (c) a + 3a (c) a + 3a
(d) 3y+ y (d) 3y+ y (d) 3y+ y
(e) 6m + 5m (e) 6m + 5m (e) 6m + 5m
(f) 3c + 2c (f) 3c + 2c (f) 3c + 2c
(g) 6x + 4x (g) 6x + 4x (g) 6x + 4x
(h) y + 10y (h) y + 10y (h) y + 10y
(i) 3r + 7r (i) 3r + 7r (i) 3r + 7r
(j) 5m + 2m (j) 5m + 2m (j) 5m + 2m
TICKET 1(b) TICKET 1(b) TICKET 1(b)
Simplify each of the following Simplify each of the following Simplify each of the following
(a) 6 + 2(2n – 8) (a) 6 + 2(2n – 8) (a) 6 + 2(2n – 8)
(b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a)
Simplify
(c) 8 – 2(n +of
each 5) the following Simplify
(c) 8 – 2(n +of
each 5) the following Simplify
(c) 8 – 2(n +of
each 5) the following
(a) 7p –+ 2(x
(d) p + 1) (a) 7p –+ 2(x
(d) p + 1) (a) 7p –+ 2(x
(d) p + 1)
(b) 52b
(e) – 2+ (w
b – 6) (b) 52b
(e) – 2+ (w
b – 6) (b) 52b
(e) – 2+ (w
b – 6)
(c) 5a–+2(1
(f) 3a – v) (c) 5a–+2(1
(f) 3a – v) (c) 5a–+2(1
(f) 3a – v)
(d) 18
(g) 3y+– y(2 – m) (d) 18
(g) 3y+– y(2 – m) (d) 18
(g) 3y+– y(2 – m)
(e) 14
(h) 6m–+3(3 5m– 2x) (e) 14
(h) 6m–+3(3 5m– 2x) (e) 14
(h) 6m–+3(3 5m– 2x)
(f) 3c + 2c
(i) 2h – 3(2h – 2) (f) 3c + 2c
(i) 2h – 3(2h – 2) (f) 3c + 2c
(i) 2h – 3(2h – 2)
(j)(g) 5m
6x +–4x3(2 – m) (j)(g) 5m
6x +–4x3(2 – m) (j)(g) 5m
6x +–4x3(2 – m)
(h) y + 10y
(k) 3p TICKET
– 4(2p – 3) 1(b) (h) y + 10y
(k) 3p TICKET
– 4(2p – 3) 1(b) (h) y + 10y
(k) 3p TICKET
– 4(2p – 3) 1(b)
Simplify +each
(i) 3r 7r of the following Simplify +each
(i) 3r 7r of the following Simplify +each
(i) 3r 7r of the following
(j) 65m
(a) + 2m– 8)
+ 2(2n (j) 65m
(a) + 2m– 8)
+ 2(2n (j) 65m
(a) + 2m– 8)
+ 2(2n
(b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a)
Simplify
(c) 8 – 2(n +of
each 5) the following Simplify
(c) 8 – 2(n +of
each 5) the following Simplify
(c) 8 – 2(n +of
each 5) the following
(a) 7p –+ 2(x
(d) p + 1) (a) 7p –+ 2(x
(d) p + 1) (a) 7p –+ 2(x
(d) p + 1)
(b) 52b
(e) – 2+ (w
b – 6) (b) 52b
(e) – 2+ (w
b – 6) (b) 52b
(e) – 2+ (w
b – 6)
(c) 5a–+2(1
(f) 3a – v) (c) 5a–+2(1
(f) 3a – v) (c) 5a–+2(1
(f) 3a – v)
(d) 18
(g) 3y+– y(2 – m) (d) 18
(g) 3y+– y(2 – m) (d) 18
(g) 3y+– y(2 – m)
(e) 14
(h) 6m–+3(3 5m– 2x) (e) 14
(h) 6m–+3(3 5m– 2x) (e) 14
(h) 6m–+3(3 5m– 2x)
(i)(f) 2h
3c –+ 3(2h
2c – 2) (i)(f) 2h
3c –+ 3(2h
2c – 2) (i)(f) 2h
3c –+ 3(2h
2c – 2)
(g) 6x + 4x
(j) 5m – 3(2 – m) (g) 6x + 4x
(j) 5m – 3(2 – m) (g) 6x + 4x
(j) 5m – 3(2 – m)
(h) 3p
(k) y +TICKET
–10y
4(2p – 3) 1(b) (h) 3p
(k) y +TICKET
–10y
4(2p – 3) 1(b) (h) 3p
(k) y +TICKET
–10y
4(2p – 3) 1(b)
Simplify each
(i) 3r + 7r of the following Simplify each
(i) 3r + 7r of the following Simplify each
(i) 3r + 7r of the following
(j) 65m
(a) + 2m– 8)
+ 2(2n (j) 65m
(a) + 2m– 8)
+ 2(2n (j) 65m
(a) + 2m– 8)
+ 2(2n
(b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a) (b) 8 –TICKET
3(v + 2) 1(a)
Simplify
(c) 8 – each 2(n +of
5) the following Simplify
(c) 8 –each 2(n +of
5) the following Simplify
(c) 8 – each 2(n +of
5) the following
(d)
(a) 7p –+ 2(x
p + 1) (d)
(a) 7p –+ 2(x
p + 1) (d)
(a) 7p –+ 2(x
p + 1)
(e)
(b) 52b – 2+ (w
b – 6) (e)
(b) 52b – 2+ (w
b – 6) (e)
(b) 52b – 2+ (w
b – 6)
(f)
(c) 5a–+2(1 3a – v) (f)
(c) 5a–+2(1 3a – v) (f)
(c) 5a–+2(1 3a – v)
(g)
(d) 183y+– y(2 – m) (g)
(d) 183y+– y(2 – m) (g)
(d) 183y+– y(2 – m)
(h)
(e) 6m–+3(3
14 5m– 2x) (h)
(e) 6m–+3(3
14 5m– 2x) (h)
(e) 6m–+3(3
14 5m– 2x)
(i)(f) 2h
3c –+ 3(2h
2c – 2) (i)(f) 2h
3c –+ 3(2h
2c – 2) (i)(f) 2h
3c –+ 3(2h
2c – 2)
(j)(g) 5m
6x +–4x 3(2 – m) (j)(g) 5m
6x +–4x 3(2 – m) (j)(g) 5m
6x +–4x 3(2 – m)
(k)
(h) 3py +TICKET
4(2p – 3) 1(b)
–10y (k)
(h) 3py +TICKET
4(2p – 3) 1(b)
–10y (k)
(h) 3py +TICKET
4(2p – 3) 1(b)
–10y
Simplify
(i) 3r +each
7r of the following Simplify
(i) 3r +each
7r of the following Simplify
(i) 3r +each
7r of the following
(a)
(j) 65m
+ 2(2n
+ 2m– 8) (a)
(j) 65m
+ 2(2n
+ 2m– 8) (a)
(j) 65m
+ 2(2n
+ 2m– 8)
(b) 8 – 3(v + 2) (b) 8 – 3(v + 2) (b) 8 – 3(v + 2)
(c) 8 – 2(n + 5) (c) 8 – 2(n + 5) (c) 8 – 2(n + 5)
(d) 7 – 2(x + 1) (d) 7 – 2(x + 1) (d) 7 – 2(x + 1)
(e) 5 – 2 (w – 6) (e) 5 – 2 (w – 6) (e) 5 – 2 (w – 6)
(f) 5 – 2(1 – v) (f) 5 – 2(1 – v) (f) 5 – 2(1 – v)
(g) 18 – (2 – m) (g) 18 – (2 – m) (g) 18 – (2 – m)
(h) 14 – 3(3 – 2x) (h) 14 – 3(3 – 2x) (h) 14 – 3(3 – 2x)
(i) 2h – 3(2h – 2) (i) 2h – 3(2h – 2) (i) 2h – 3(2h – 2)
(j) 5m – 3(2 – m) (j) 5m – 3(2 – m) (j) 5m – 3(2 – m)
TICKET 1(c) TICKET 1(c) TICKET 1(c)
Simplify each of the following Simplify each of the following Simplify each of the following
(a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f)
(b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p)
(c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2)
(d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7)
(e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7)
(f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p)
(g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7)
(h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2)
TICKET 1(c) TICKET 1(c) TICKET 1(c)
Simplify each of the following Simplify each of the following Simplify each of the following
(a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f)
(b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p)
(c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2)
(d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7)
(e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7)
(f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p)
(g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7)
(h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2)

TICKET 1(c) TICKET 1(c) TICKET 1(c)


Simplify each of the following Simplify each of the following Simplify each of the following
(a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f)
(b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p)
(c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2)
(d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7)
(e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7)
(f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p)
(g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7)
(h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2)

TICKET 1(c) TICKET 1(c) TICKET 1(c)


Simplify each of the following Simplify each of the following Simplify each of the following
(a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f) (a) 3(2f – 5) – (3 – 2f)
(b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p) (b) (2p – 3) – (4 – 3p)
(c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2) (c) (4e – 3) – 6(e – 2)
(d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7) (d) (3f + 1) – (4f – 7)
(e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7) (e) (3b + 1) – (2b – 7)
(f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p) (f) (2p – 3) – (4 – 3p)
(g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7) (g) 5(3p + 3) – 3(2p – 7)
(h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2) (h) 7(2p + 1) – 4(3p + 2)
TICKET 1(d) TICKET 1(d) TICKET 1(d)
Simplify each of the following Simplify each of the following Simplify each of the following
–9y – 3(y – 2) –9y – 3(y – 2) (a) –9y – 3(y – 2)
(2x – y) – (x – 5y) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y)
2x – 2(3 – x) 2x – 2(3 – x) (c) 2x – 2(3 – x)
3[m – 2(m – 4)] 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)]
–7x – 4(x – 5) –7x – 4(x – 5) (e) –7x – 4(x – 5)
–4(3 + q) + 6q – 2 –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2
4[2x – 4(x – 3)] 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)]
7q – 3 – 5(2 + q) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q)
–3h – 4(6 – 5h) – 7 –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7
–6(1 – 2x) + 4x + 10 –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10
(k) 3p – 4(2p – 3) (k) 3p – 4(2p – 3)

TICKET 1(d) TICKET 1(d) TICKET 1(d)


Simplify each of the following Simplify each of the following Simplify each of the following
(a) –9y – 3(y – 2) (a) –9y – 3(y – 2) (a) –9y – 3(y – 2)
(b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y)
(c) 2x – 2(3 – x) (c) 2x – 2(3 – x) (c) 2x – 2(3 – x)
(d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)]
(e) –7x – 4(x – 5) (e) –7x – 4(x – 5) (e) –7x – 4(x – 5)
(f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2
(g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)]
(h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q)
(i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7
(j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10
TICKET 1(d) TICKET 1(d) TICKET 1(d)
Simplify each of the following Simplify each of the following Simplify each of the following
(a) –9y – 3(y – 2) (a) –9y – 3(y – 2) (a) –9y – 3(y – 2)
(b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y)
(c) 2x – 2(3 – x) (c) 2x – 2(3 – x) (c) 2x – 2(3 – x)
(d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)]
(e) –7x – 4(x – 5) (e) –7x – 4(x – 5) (e) –7x – 4(x – 5)
(f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2
(g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)]
(h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q)
(i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7
(j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10
TICKET 1(d) TICKET 1(d) TICKET 1(d)
Simplify each of the following Simplify each of the following Simplify each of the following
(a) –9y – 3(y – 2) (a) –9y – 3(y – 2) (a) –9y – 3(y – 2)
(b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y) (b) (2x – y) – (x – 5y)
(c) 2x – 2(3 – x) (c) 2x – 2(3 – x) (c) 2x – 2(3 – x)
(d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)] (d) 3[m – 2(m – 4)]
(e) –7x – 4(x – 5) (e) –7x – 4(x – 5) (e) –7x – 4(x – 5)
(f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2 (f) –4(3 + q) + 6q – 2
(g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)] (g) 4[2x – 4(x – 3)]
(h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q) (h) 7q – 3 – 5(2 + q)
(i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7 (i) –3h – 4(6 – 5h) – 7
(j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10 (j) –6(1 – 2x) + 4x + 10

TICKET 1(e) TICKET 1(e) TICKET 1(e)


Simplify each of the following Simplify each of the following Simplify each of the following
a) (4e – 3) – 6(e – 2) a) (4e – 3) – 6(e – 2) a) (4e – 3) – 6(e – 2)
b) 14 – 3(3 – 2x) b) 14 – 3(3 – 2x) b) 14 – 3(3 – 2x)
c) 6 + 2(2n – 8) c) 6 + 2(2n – 8) c) 6 + 2(2n – 8)
d) (3f + 1) – (4f – 7) d) (3f + 1) – (4f – 7) d) (3f + 1) – (4f – 7)
e) 5m – 3(2 – m) e) 5m – 3(2 – m) e) 5m – 3(2 – m)
f) (3b + 1) – (2b – 7) f) (3b + 1) – (2b – 7) f) (3b + 1) – (2b – 7)
g) 8 – 2(n + 5) g) 8 – 2(n + 5) g) 8 – 2(n + 5)
h) 7(2p + 1) – 4(3p + 2) h) 7(2p + 1) – 4(3p + 2) h) 7(2p + 1) – 4(3p + 2)
i) (2p – 3) – (4 – 3p) i) (2p – 3) – (4 – 3p) i) (2p – 3) – (4 – 3p)
j) 5(3p + 3) – 3(2p – 7) j) 5(3p + 3) – 3(2p – 7) j) 5(3p + 3) – 3(2p – 7)
TICKET 1(f) TICKET 1(f) TICKET 1(f)
(a) (a) (a)
(b) (b) (b)
(c) (c) (c)
(d) (d) (d)
(e) (e) (e)
TICKET 1(g) TICKET 1(h) TICKET 1(i)
Simplify each of the Simplify 2k  3 k  2
(a) 
following as a single fraction 1 m2 3 2
(a) 
in its simplest form. 2 m 6m 2 n n 62

7 5m  2 (b) 
 h3 2h 3 12n
(a) (b) 
12 m 12m 2 3h h 3 h k  h
7 m4 1 3 r (c) 
(b)  (c)  3h hk
12m 4m 2 3k 12kr 3k  m 6  m
e9 e3f 5 h2 (d) 
(c)  (d)  mk 2m
6e 2ef 6e 2eh 3x 3y

4 12 2 h  1 4  e (e)
x  2 x  x  2
(d)  (e) 
x  3 x  x  3 eh 2e
2004 2005
Simplify (3x-1)2 – (7x + 4) [2 marks] Simplify (2p – q)2 + q(4p – q) [2 marks]

2006 2008
Simplify 3(2p – 5) + (p – 3)2 [2 marks] Simplify 2p – 3q – (p + 5q) [2 marks]

2009 2011
Simplify each of the following expressions: Simplify each of the following expressions:
(a) 2  n  5   3 (a) n   p  2n 
(b) 3  4m  3k    5k  m  [3 marks] (b) 6d  5ef
[3 marks]
2de

MELAKA TRIAL 2010 KEDAH TRIAL 2010


Simplify each of the following expressions : Simplify each of the following expressions:
(a) 9  2  a  3 (a) 5 y (1  y )
(b)  2m  3n  2  12mn [3
(b) 2  3 p  q    4q  p  [3 marks]
marks]
KEDAH TRIAL 2011 SARAWAK TRIAL 2011
Simplify  3m  2n   12mn Simplify  m  5   5  3  2m 
2 2
[2 marks] [2 marks]

PAHANG TRIAL 2011 SABAH TRIAL 2011


Simplify  m  3  2  6m  1 Simplify  2 x  1  4 x 2
2 2
[2 marks] [2 marks]

PULAU PINANG TRIAL 2011 NEGERI SEMBILAN TRIAL 2011


Simplify 6a   a  3 [2 marks] Simplify  5m  n   5m2
2 2
[2 marks]

PERAK TRIAL 2010 PERAK TRIAL 2011


Simplify each of the following expression : Simplify each of the following expressions:
(a)  15  20 y   5 (a) 3  p  4   2
(b)  7 x  2 y   4  x  y  (b) 2 xy  7 y 2   x  y 
2
[3 marks] [3 marks]

PERLIS TRIAL 2010 NEGERI SEMBILAN TRIAL 2010


Simplify each of the following expression: Simplify each of the following expression:
(a) 3  2 1 x (a) 3  p  2   6
(b) 3  2  x   5 x  1 [3 marks] (b)  2 x  1   x  3
2
[3 marks]
SBP TRIAL 2010 SABAH TRIAL 2010
2 x2  8x 10 x 2 y 2
Simplify [2 marks] Simplify [3
x 2  16 5 xy 2  10 yx 2
marks]

PMR past year questions

2007 2008
Expand each of the following expressions : Expand each of the following expressions :
(a)q(2 + p) (a)2g ( 5 – k)
(b) ( 3m – n)2 [3 marks] (b) ( h – 5)(3h + 2) [3 marks]

2010 NEGERI SEMBILAN TRIAL 2011


Expand 3  2 x  1 [1 mark] Expand 2 y  4 x  3 [1 mark]

WILAYAH PERSEKUTUAN TRIAL 2011 PERLIS TRIAL 2011


Expand each of the following expressions : Expand each of the following expressions :
(a) 3  x  7  (a) 2  x  6 
(b)  m  4n   8mn (b)  3m  n 
2 2
[3 marks] [3 marks]

TERENGGANU TRIAL 2011 SELANGOR TRIAL 2011


Expand each of the following expressions : Expand each of the following expressions :
(a) 3  2 x  3 y  (a) 9  2a  3
(b)  m  2   m  3 [3 marks] (b)  7  3 g   4  5 g  [3 marks]
KELANTAN TRIAL 2011 JOHOR TRIAL 2011
Expand each of the following expressions: Expand each of the following expressions:
(a) 2  9  x  (a) 5  q  3
(b)  2 y  3  y  3   y  3 (b)  2 x  5 
2
[3 marks] [3 marks]

KEDAH TRIAL 2011 SABAH TRIAL 2011


Expand 2 p  1  p  [1 mark] Expand  p  3  2q  [1 mark]

SBP TRIAL 2011 SBP TRIAL 2010


Expand each of the following. Expand:
(a)  3  2 p  1
2
(a)  4 x  y 
2
(b) 2m  m  n    m  n 
2
[3 marks]
(b)  2 x  3 y   2 xy
2
[3 marks]

SARAWAK TRIAL 2011 TERENGGANU TRIAL 2010


Expand 4  t  2   3 [1 mark] Expand  p  6 
2
[2 marks]

PAHANG TRIAL 2010 KEDAH TRIAL 2009


Expand each of the following expressions: Expand each of the following expressions:
(a) 4x  x  y  (a) 3( 7 + 2n )
(b)  2 x  y   x  2 y  [3 marks] (b) ( 2p – 3 )2 [3 marks]

TERENGGANU TRIAL 2009 JOHOR TRIAL 2010


Expand each of the following expressions: Expand each of the following expressions:
(a) 4 e  3 f  (a) 3u  7  w 
(b)  p  2 2 [3 marks]
(b) 17 m  3  2  5m  [3 marks]

PMR past year questions

2004 2005
Factorise completely Factorise completely each of the following
(a)9xy -3x2 expressions :
(b) p2 – 6(p+1) – (8 – p) [3 marks] (a)4e – 12ef
(b) 3x2 – 48 [3 marks]

2006 2009
Factorise completely 50 – 2m2 [2 marks] Factorise completely 5  20k 2 [2 marks]

2007 2010
Factorise completely each of the following Factorise completely each of the following
expressions : expressions :
(a)2y + 6 (a) 5 p  10
(b) 12 – 3x2 [3 marks] (b) 3x 2  12 x  12 [3 marks]

2011 PERLIS TRIAL 2011


Factorise completely each of the following Factorise completely each of the following
expressions : expressions :
(a) 3m  mk (a) p 2  8 pq
(b) 4x  xy 2 [3 marks] (b) mx  2m  3 x  6 [3 marks]
KEDAH TRIAL 2011 SBP TRIAL 2011
Factorise completely: Factorise completely:
mn  3mp  2n  6 p [2 marks] 3 pr  6 p  3qr  6q [2 marks]

NEGERI SEMBILAN TRIAL 2011 SABAH TRIAL 2011


Factorise completely each of the following Factorise completely each of the following
expressions : expressions :
(a) 32  8m (a) 2  14k
(b) 100  4x 2 [3 marks] (b) 8 x 2  18 y 2 [3 marks]

WILAYAH PERSEKUTUAN TRIAL 2011 TERENGGANU TRIAL 2011


Factorise completely each of the following Factorise completely each of the following
expressions : expressions :
(a) 27 x  9 xy (a) 3x 2  27
(b) 25 x 2  81 y 2 [3 marks] (b) 3 p 2  24 p  48 [3 marks]

SELANGOR TRIAL 2011 PAHANG TRIAL 2011


Factorise completely each of the following Factorise completely each of the following
expressions : expressions :
(a) 12d  4dm (a) p 2  7 p
(b) 3a 2  75b 2 [3 marks] (b) 3  27 p 2 [3 marks]

PULAU PINANG TRIAL 2011 KELANTAN TRIAL 2011


Factorise completely each of the following Factorise completely each of the following
expressions : expressions
(a) 8 p  32 pq (a) 3 p  9q
(b) 5a 2  5 [3 marks] (b) 9 pq  3 pr  6q  2r [3 marks]
JOHOR TRIAL 2011 PERAK TRIAL 2011
Factorise completely each of the following Factorise completely:
expressions: (a) 9a  45
(a) 4k  8 (b) 7 x  7 y  xy  y 2 [3 marks]
(b) 3m2  75n 2 [3 marks]

PMR past year questions

2004
 1 
3 1 p 
  2 
Express 2m  mp 
as a single fraction in its simplest form. [3 marks]
 
 

2005
1 m2
Express  as a single fraction in its simplest form. [3
2m 6 m 2
marks]

2006
1 5  2v
Express  as a single fraction in its simplest form. [3
5m 15mv
marks]

2007
5 2  3w
Express  as a single fraction in its simplest form. [3
3n 6n
marks]

2008
1 n4
Express  as a single fraction in its simplest form. [3 marks]
n 3n

2009
3 k  15
Express  as a single fraction in its simplest form. [3 marks]
5m 10mk

2010
3 2p7
Express  as a single fraction in its simplest form. [3 marks]
4q 12q

2011
7m m  6
Express  as a single fraction in its simplest form. [3 marks]
4 12

PERLIS TRIAL 2011


8m m  6 h
Express  as a single fraction in its simplest form. [3 marks]
12h 6h

WILAYAH PERSEKUTUAN TRIAL 2011


1 m 1
Express  as a single fraction in its simplest form. [3 marks]
3 2m

TERENGGANU TRIAL 2011


1 n8
Express  as a single fraction in its simplest form. [3 marks]
2n 6 n 2

SELANGOR TRIAL 2011


3 2d  4
Express  as a single fraction in its simplest form. [3 marks]
2d 4d 2

PAHANG TRIAL 2011

m m4
Express  as a single fraction in its simplest form.
2n 6n

MELAKA TRIAL 2011

NEGERI SEMBILAN TRIAL 2011


\

KEDAH TRIAL 2011

5 2q
Express  as a single fraction in its simplest form.
6 p 18 pq

KELANTAN TRIAL 2011


3 3  3x
Express  as a single fraction in its simplest form.
5 y 15 xy

JOHOR TRIAL 2011


2 7q  4
Express  as a single fractin in its simplest form.
3 p 15 pq

PERAK TRIAL 2011


PULAU PINANG TRIAL 2011

SABAH TRIAL 2011

SARAWAK TRIAL 2011

SBP TRIAL 2011


SARAWAK TRIAL 2011

MELAKA TRIAL 2010


Factorise completely 81m2 – 9 (2 marks)

MELAKA TRIAL 2010


2 6p 3
Express  as a single fraction in its simplest form. (3 marks)
p 3p

You might also like